Evolução da estrutura de apresentação do balanço patrimonial nos últimos setenta anos: do Decreto Lei nº 2.627/40 à Lei nº 11.638/07 - Costa, Renato Goulart da (2010)
Together, the globalization and the international capital market development have brought up the need for a set of international accounting rules, with the aim to facilitate the information comparison among enterprises from the same economic sector around the world. So, it started in Brazil an effort from Academic and Regulatory Organs to update the Join Stock Corporation Brazilian Law ( Lei das Sociedades anônimas ), edited in 1976. The publication of such law was considered a very important event back at that time, for it adjusted and altered the former Decree Law nº 2.627/40, considered by many as the first Join Stock Corporation Brazilian Law. Upon exposing the reasons that followed the Project for revising and altering the accounting part of the Law nº 6.404/76, it was presented as plausible justifications the upcoming of a new Brazilian economic reality, different from the one in 1976, when the Law was edited and it was necessary to start capitals, through acquiring cheaper resources by Brazilian enterprises. As a means to beneficiate from the adequation process in the Brazilian legislation, it was originated in 2005 the Accounting Pronouncement Committee ( Comitê de Pronunciamentos Contábeis CPC ), aiming for its country to obtain important developments in the updating and modernization of rules and accounting principles. All the efforts resulted in the publication of the Laws nº 11.638/07 and 11.941/09, which altered many aspects of the actual 1976 Law, for example, the criteria for classification and measuring of the enterprises assets, liabilities and equity, parts of the Balance Sheet. After the regulatory limit, the CPC has defined a schedule for all the Brazilian accounting rules, according to the international rules, up to 2010. Such rules must be implemented, but for some exceptions, for all join stock corporations and for those depending on the specific regulation edited by a Regulatory Organ. In this context, the aim of this work is to analyze the evolution of the presentation structure of the Balance Sheet from open enterprises and their main alterations in the last seventy years, since the promulgation of the Decree Law nº 2.627/40, until the publication of the Law nº 11.638/07. It can be highlighted the concept of fair value, which reinforces the prevalence of the economic essence over the juridical way, among others. This work also includes some examples in which it is analyzed and demonstrated the development of publication models of the Balance sheet applied by the Join Stock Companies concerning the legislation of that time